2010
DOI: 10.1371/journal.pone.0012190
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Gene Expression Following Coxiella burnetii Infection in Mice: Potential Role of Circadian Rhythm

Abstract: BackgroundQ fever, a zoonosis due to Coxiella burnetii infection, exhibits sexual dimorphism; men are affected more frequently and severely than women for a given exposure. Here we explore whether the severity of C. burnetii infection in mice is related to differences in male and female gene expression profiles.Methodology/Principal FindingsMice were infected with C. burnetii for 24 hours, and gene expression was measured in liver cells using microarrays. Multiclass analysis identified 2,777 probes for which e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 63 publications
2
33
1
Order By: Relevance
“…In a human-based study, 3 it was found that sex was related with C. burnetii infection, where men were 2.5 times more likely to be infected with the pathogen than women; the same result was also reported in mice in a laboratory-based study. 16 However, the results of our study were different; no significant association was found between C. burnetii infection and sex in wild rodents.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…In a human-based study, 3 it was found that sex was related with C. burnetii infection, where men were 2.5 times more likely to be infected with the pathogen than women; the same result was also reported in mice in a laboratory-based study. 16 However, the results of our study were different; no significant association was found between C. burnetii infection and sex in wild rodents.…”
Section: Discussioncontrasting
confidence: 86%
“…However, it is difficult to compare these findings with those reported in other works, which present information on the presence of antibodies to C. burnetii in rodents. [13][14][15][16] The statistical results showed that weight was associated with C. burnetii infection, possibly because larger rodents become matured and move widely and have more chances to be infected with C. burnetii. The reason for the association between month of capture and C. burnetii infection may be the temperature differences between months.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34][35][36] Males generally exhibit lower immune responses than females. 22,31,37 The phagocytic activity of macrophages and production of inflammatory cytokines are higher in females than in males.…”
Section: Discussionmentioning
confidence: 99%
“…10Y12 We recently found that Coxiella burnetii infection is associated with sex-specific modulation of the CLOCK, ARNTL, and PER2 genes. 12,13 It is unclear whether these changes are related to the presence of bacteria or to the development of an inflammatory response. We hypothesized that the sex-related modulation of these genes is not restricted to Q fever but may be induced by the inflammatory response, independent of infection.…”
mentioning
confidence: 99%